2021
DOI: 10.3389/fimmu.2020.607891
|View full text |Cite
|
Sign up to set email alerts
|

MAPKAP Kinase-2 Drives Expression of Angiogenic Factors by Tumor-Associated Macrophages in a Model of Inflammation-Induced Colon Cancer

Abstract: Chronic inflammation increases the risk for colorectal cancer through a variety of mechanisms involving the tumor microenvironment. MAPK-activated protein kinase 2 (MK2), a major effector of the p38 MAPK stress and DNA damage response signaling pathway, and a critical regulator of pro-inflammatory cytokine production, has been identified as a key contributor to colon tumorigenesis under conditions of chronic inflammation. We have previously described how genetic inactivation of MK2 in an inflammatory model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 87 publications
(93 reference statements)
1
16
1
Order By: Relevance
“…One possible explanation for our data diverging from previously published work is that many of these utilized different cancer types (i.e. intestinal tumors) or murine models (61)(62)(63)(64)(65). However, in patient derived data from TCGA, we note a significant association with improved 2-year survival in lung adenocarcinoma with high MK2 expression, Figure 5 Our data clearly show that a non-kinase function of MK2 is responsible for the observed sensitization to cell death, Figure 9.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…One possible explanation for our data diverging from previously published work is that many of these utilized different cancer types (i.e. intestinal tumors) or murine models (61)(62)(63)(64)(65). However, in patient derived data from TCGA, we note a significant association with improved 2-year survival in lung adenocarcinoma with high MK2 expression, Figure 5 Our data clearly show that a non-kinase function of MK2 is responsible for the observed sensitization to cell death, Figure 9.…”
Section: Discussioncontrasting
confidence: 74%
“…Interestingly, the majority of data showing a role for MK2 in cancers focus on MK2 kinase activity and its role in tumor development (61)(62)(63)(64). In a novel murine model of NSCLC that generates MK2-proficient and MK2-deficient tumors within the same animal, Morandell et al show that MK2-proficient tumor area is consistently greater than MK2-deficient tumor area (65).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 stimulates macrophages to secrete the soluble factors MMP-2 and MMP-9, which effectively promote cancer cellinduced angiogenesis in vivo [84]. By adoptive transfer of WT macrophages into MK2 KO mice, Suarez-Lopez, L. et al demonstrated that MK2 signaling/angiogenesis is inherent in macrophages; MK2 regulates CXCL12 expression in TAMs, promoting angiogenesis and progression of cancer cells [85]. Luput, L. and his team demonstrated that TAMs can enhance the expression of angiogenic proteins in the TME by regulating the activity of NADPH oxidase, which maintains the redox status and angiogenic capacity in the TME of CRC [64].…”
Section: Tams Enhance Angiogenesis In Crcmentioning
confidence: 99%
“…A recent work demonstrated for the first time, using a mouse model of IBD-CRC, that the M2 macrophage polarization could be altered by genetic inactivation of the MAPK-activated protein kinase 2 (MK2), resulting in delayed tumor progression (Suarez-Lopez et al, 2020).…”
Section: Grivennikov Et Al (2009)mentioning
confidence: 99%